Route Optimization of Offshore Lifelines Taking Into Account Potential Earthquake-Related Geohazards - Makrakis, Nikolaos; Psarropoulos, Prodromos N.; Chatzidakis, Dionysios; Tsompanakis, Yiannis (Frontiers in Built Environment, 2020)
Offshore lifelines, such as gas pipelines and cables, consist large-scale and very important engineering projects, while their safe operation is undoubtedly a challenging task. Offshore lifelines usually cross submarine areas facing various offshore geohazards, which are very often related (directly or indirectly) with local seismicity. Therefore, in order to avoid severe damages with devastating consequences, it is of paramount importance to optimize their design, taking realistically into account all earthquake-related geohazards and their detrimental effects on the examined lifeline. Since the avoidance of all geohazardous areas is not always feasible, the route optimization of a lifeline at an early stage of the design phase is very crucial for its safety and serviceability. The current study presents a new smart decision-support tool that aims to facilitate route optimization of offshore lifelines through: (a) the qualitative and quantitative assessment of the major earthquake-related geohazards along a possible lifeline routing, (b) the quantitative assessment of their potential impact on the lifeline, and (c) the selection of the optimum lifeline route. The proposed decision-support tool can be very useful for the efficient design of an offshore lifeline, provided that adequate and reliable input data are available. Its efficiency is illustrated with two characteristic case studies in the Mediterranean Sea.